AKURASI PENJEJAKAN OBJEK DALAM BERAGAM RUANG WARNA - Sukadarmika, Gede; Wiharta, Dewa Made; Sastra, Nyoman Putra (Jurnal Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi Elektro, 2015)
The object trace has been a problem in estimating an object position when the object is moving due to the heavy influence of the uncertainty. Many researcher claim that color histogram is reliable feature to represent this object. . Different investigators use different color spaces in conducting research on tracking the object. So, there is no numerical comparison of the impact of the use of different color spaces to the successful tracking. This study compare the performance of tracking an object by using a different color space i.e.: RGB, HSV, and CIELAB. The performance is shown numerically by comparing the actual position of the object with the results of the estimation.
Keywords: Penjajakan objek, ruang warna, RGB, HSV, CIELAB